The Importance of Financial Literacy Education - holik, abdul (Adpebi International Journal of Multidisciplinary Sciences, 2022)
ABSTRACT Purpose – This research tries to explore the importance of financial literacy education as a provision of life for everyone. We consider this problem due to many people must face financial difficulties in their old age. Methodology/approach – We use qualitative analysis with in-depth and critical analysis. This research uses a qualitative approach, which is a study of literature. Some papers and books regarding financial literacy used as references for this study. This research focus examines the importance of financial literacy education for the younger generations explicitly, as a provision for them to live their lives in the future. Findings – Our result shows that the role of family and school can shape people in understanding financial knowledge nicely. We elaborate these variables as important factors that influencing life. Novelty/value – Our finding suggests that financial literacy education must be started since childhood due to its stage crucial in someone’s life phase, and also children are easy to receive lessons. We also show that teachers are essential in educating children promptly to know financial matters. A large amount of fraud cases that makes people loss a lot of money, is due to the ignorance of financial literacy. By mastering knowledge of wealth people can live in prosperous life. Keywords: Financial Literacy, Youth, Prosperous Life